MicroRNAs modulation by isodrimeninol from Drimys winteri in periodontitis-associated cellular models: preliminary results - Rodríguez, Nelia M.; Loren, Pía; Paez, Isis; Burgos, Viviana; Martínez-Cardozo, Constanza; Chaparro, Alejandra; Salazar, Luis A. (Frontiers in Oral Health, 2025)
IntroductionPeriodontitis is a chronic inflammatory disease characterized by the progressive destruction of the tooth's supporting tissues, driven by complex interactions between periodontopathogenic bacteria, environmental factors, and the host immune response. MicroRNAs (miRNAs) have emerged as key modulators of inflammatory pathways and are increasingly recognized for their role in the pathogenesis of periodontitis. Their deregulation in this disease suggests potential therapeutic applications targeting miRNA expression. Natural compounds such as isodrimeninol, derived from Drimys winteri (Dw), may offer novel approaches to modulate miRNA activity due to their antiinflammatory properties. However, no studies have previously linked this sesquiterpene to miRNA regulation in periodontitis. This study investigates the in vitro effects of isodrimeninol on six miRNAs (miR-17-3p, miR-21-3p, miR-21-5p, miR-146a-5p, miR-155-5p, and miR-223-3p) associated with periodontitis using two cellular models.MethodsSaos-2 cells (osteoblast-like cells) and periodontal ligament-derived mesenchymal stromal cells (hPDL-MSCs). Both cell types were stimulated with lipopolysaccharide (LPS) to induce inflammation and treated with isodrimeninol and resveratrol for comparison.ResultsIsodrimeninol reduced Interleukin-1beta (IL-1β) and Interleukin-6 (IL-6) gene expression and caused differential expression patterns of the miRNAs examined, upregulating miR-146a-5p and miR-223-3p, while downregulating miR-17-3p, miR-21-3p, miR-21-5p, and miR-155-5p (p < 0.05).ConclusionThese findings indicate a connection between miRNAs, periodontitis, and the regulation of inflammation by isodrimeninol, providing potential opportunities for the treatment. However, further validation is needed to confirm these results.